Plan de seguridad en el trabajo para prevenir accidentes laborales en la Clínica Nataly de la ciudad de Loja - Huanga Ordoñez, Leonardo Jasiel (2024)
The purpose of this paper entitled "Occupational Safety Plan to prevent occupational accidents at the Nataly Clinic in the city of Loja" was to develop an Occupational Safety Plan to prevent occupational accidents inside the Clinic's facilities. For the elaboration of this research, it was used the non-experimental descriptive type and design, the bibliographic review technique, direct observation through the questionnaires of the National Institute of Occupational Safety and Health (INSST), an interview with the company’s general manager, a survey applied to 21 of the Clinic’s staff; this information allowed us to get fully informed of the current situation in terms of occupational safety at work. In the results it was evidenced that the clinic, in terms of safety signage, workplaces and fires and explosions; complies with the regulations with an adequate accident prevention process, as no occupational accidents have been reported since its implementation; in addition, the risks to which workers are exposed are clearly identified. However, it does not have a public document where the prevention measures are plainly established. Based on the information obtained, in the socialization it was presented the proposal for a safety plan that details the regulations, obligations and responsibilities of both the staff and the manager/employer.